Urinary disorders in patients diagnosed with organic brain pathology - P. P. Palatkin; N. G. Konovalova; O. V. Zhatko (Вестник урологии, 2024)
Introduction. This study is relevant due to the high prevalence of organic brain pathology and the negative influence of urination disorders on the quality of life.Objective. To analyse the impaired function of lower urinary tracts in patients with organic brain pathology.Materials & methods. We analysed 607 patients with severe organic brain pathology (105 had traumatic spinal cord injury (TSCI) and 457 had consequences of acute stroke (AS)). We performed clinical urological examinations. During the survey, attention was paid to the presence of urinary tract pathology at the examining time and anamnesis. Structural changes in the urinary tract were objectively assessed. We objectively assessed structural changes in urinary tracts including prostate adenoma in men, insufficiency of pelvic floor muscles in women and strictures of the urethra or ureters. The degree of the spastic syndrome was assessed with the Ashworth Scale. The neurourological examination included cystometry with the measurement of bladder volume and post-void residual urine. The cognitive status of the patients was assessed with the MMSE (Mini-Mental State Examination) questionnaire. The correlation analysis between the degree of spastic syndrome measured with the Ashworth Scale and urination disorders was performed with Spearman rank correlation.Results. All patients had neurogenic dysfunction of the lower urinary tract. A combination of bladder retention and emptying disorders was found in 62 men older than 45yo with benign prostate hyperplasia (10,2% of all cases). An impaired accumulation function in history was found in 45 women older than 45yo (7,4% of all observations). The level of spasticity was 3 or 4 points on the Ashworth Scale in patients with TSCI and 2 to 4 points in those with AS. The analysis of correlations between the degree of spasticity and urination disorders showed a moderate relationship (r = 0,4) in patients with TSCI and a medium relationship (r = 0.65) in patients with AS.Conclusion. Neurogenic dysfunction of the lower urinary tract accompanies patients with severe organic brain pathology throughout their life and requires adequate correction.